The prognostic value of NPT test combined with amplitude integrated electroencephalogram in children with VE and its bioreliability analysis: NPT combined with AEEG in children with VE - Liu, Yinghong; Li, Wenjuan; Wang, Chaohai; Chen, Shuyun; Wang, Gaiqing (Journal of Medical Biochemistry, 2023)
Background: Viral encephalitis (VE) as one of the common diseases of children intracranial infection, it has come on urgent, progress is fast, the clinical features of severe cases may even lead to disability, death and other serious adverse prognostic outcomes, so seek in early diagnosis and prognosis of efficiency of the relevant indicators to stop in time and take effective means to prevent the further development is of great significance. Neopterin (NPT), as a factor that plays an important role in the process of validation development, has been relatively rarely studied in children with VE. Methods: In this study, 127 cases of children with VE were retrieved from TCGA database by bioinformatics, and their amplitude integrated electroencephalogram (AEEG) related information was collected at the same time. The neurodevelopmental status of VE children was evaluated according to Gesell scale and divided into good group (n=88) and poor group (n=39). The differences in NPT expression and AEEG score between them were observed. In addition, the clinical data of 100 children without VE were screened from the database, and the differences in NPT expression and AEEG score between VE children and non-VE children were compared. ROC curve was used to evaluate the clinical efficacy of NPT combined with AEEG in diagnosis and prognosis prediction. Kaplan-meier was used to observe the effect of NPT high expression and low expression on poor prognosis of VE children. Results: Compared with the non-VE children, the VE children had higher NPT and lower AEEG score, while the poor group had higher NPT and lower AEEG score. The ROC curve showed that the area under the curve of NPT combined with AEEG for the diagnosis and prognosis prediction of VE were 0.892 and 0.884, respectively, which were higher than those of single NPT or AEEG, indicating that the combined detection has high clinical value not only for diagnosis, but also for prediction and prognosis. Kaplan-meier survival curves showed that high NPT expression often predicted poor prognosis. Conclusions: The combination of NPT and AEEG can be used to timely and effectively evaluate the condition of children with VE in the process of clinical practice.